The role of Traditional Birth Attendants (TBAs) in the mapping strategy of pregnant women in sub-urban areas - Ismainar, Hetty; Triana, Ani; Marlina, Hastuti (Technium Social Sciences Journal, 2021)
In Indonesia, there are still many Traditional Birth Attendants (TBAs) in sub-urban areas. The research objective was to determine the role of TBAs in mapping pregnant women in the region. A qualitative, exploratory study was conducted between April-August 2019. The location of this study was in four sub-districts in Dumai City, Riau Province. A total of 14 informants consisted of TBAs, midwives, heads of the health center, and pregnant women. Data collected through semi-structured interviews and focus group discussions based on informant responses, presented in narrative form, and used thematic analysis. The results showed that TBAs still received pregnancy checks, assisting birth at home, body massages, assisted childbirth, and performed rituals during pregnancy. Pregnant women still come to TBAs, which have become a hereditary habit, and believe in myths. Lack of transportation to health facilities, feel comfortable with the friendliness of TBAs, lack of communication and seem to close access to health workers. Conclusion. The role of Traditional Birth Attendants has not active in reported of pregnant women in their areas. So that health workers find it difficult to do the mapping strategy. Suggestion, it is necessary to establish "TBAs Care" as a forum for communication between TBAs and health workers. Thus, it can increase the active role of TBAs in the mapping strategy of pregnant women